Achievement of nutritional goals after a pediatric intensive care unit nutrition support guideline implementation. (August 2022) - Rungsattatharm, Lalin; Kongkiattikul, Lalida; Samransamruajkit, Rujipat; Chomtho, Sirinuch
Summary: Background and aims: A nutrition support guideline was developed and implemented in a pediatric intensive care unit (PICU) to improve the nutritional management of patients. This study aimed to evaluate the impact of this guideline on achieving energy and protein delivery goals. Methods: Medical records of the patients admitted in the PICU from August 2015 to April 2017 were retrospectively reviewed. Patients who stayed in the PICU for less than 24 h or had an inborn error of metabolism were excluded. Achievement of nutritional goals was compared between the patients during the pre-implementation period (August to October 2015) and post-implementation period (November 2015 to April 2017) of the guideline. Subgroup analysis by protocol compliance was conducted in the post-implementation group. Results: A total of 215 patients were included in the study (53 pre-implementation, 162 post-implementation). There were no differences between the two groups in patient characteristics, time to start enteral nutrition, time to reach the energy delivery goal, time to reach the protein delivery goal, and proportion of the patients who reached each goal. In the post-implementation group, parenteral nutrition was delayed to three days compared with one day in pre-implementation (p = 0.027) and the proportion of patients who did not receive nutrition support was lower (3.1% vs 9.4% pre-implementation, p = 0.043). Subgroup analysis in the post-implementation group showed that 69.7% of the patients were protocol compliant, of which the time to reach the energy delivery goal (59 vs 103 h, p < 0.001) and protein delivery goal (64 vs 135 h, p = 0.02) were significantly shorter compared with the non-compliant group. Moreover, the proportion of the patients who reached the energy delivery goal (75.2% vs 24.5%, p < 0.001) and protein delivery goal (56.6% vs 12.2%, p < 0.001) were higher in the compliant group. Conclusions: Compliance with the nutrition support guideline significantly improved the achievements in delivering energy and protein to patients in PICU. Increasing compliance with the guideline may improve clinical outcomes in PICU patients.